Social impact bonds: Financing grassroots sports - I. V. Solntsev (Финансы: теория и практика, 2021)
This paper aims to analyze the foreign experience of using social impact bonds (SIB) and formulate proposals for the application of this tool in financing projects aimed at developing mass sports and increasing physical activity on a national scale. The scientific novelty of the article is confirmed by the limited application of such a mechanism in Russia and its insufficient study. This research aims to fill this academic and applied gap. The author uses the methods of deconstruction and aspect analysis. The article analyzes in detail the foreign experience of using social impact bonds, reveals the advantages and disadvantages of this model. In the absence of SIB sports projects, the model of social impact bonds is considered through the example of a New York City-based program aimed at reducing the recidivism rate among young people. This example allowed the author to describe the interaction scheme for all participants and stakeholders and to illustrate related advantages and disadvantages. In the future, this model can be introduced into Russian practice and used as a model for launching a similar project in the field of grassroots sports. The analysis of successful projects implemented abroad allowed the author to substantiate the possibility of using social impact bonds in financing programs aimed at increasing population levels of physical activity. A system of target indicators is proposed, including such a metric as social return on investment (SROI). The author describes in detail the methodology for calculating SROI and provides examples of calculating this indicator for mass sports projects. The author concludes that the advantages of SIB prevail over the disadvantages and about the high potential of this tool. Further research in this area can be aimed at clarifying the methodology for calculating the SROI for sport interventions promoting physical activity at the population level and evaluating specific projects in the field.